A Chemical Vapor Deposition Diamond Reactor for Controlled Thin‐Film Growth with Sharp Layer Interfaces. Issue 4 (12th August 2022) - Schätzle, Philip; Reinke, Philipp; Herrling, David; Götze, Arne; Lindner, Lukas; Jeske, Jan; Kirste, Lutz; Knittel, Peter
Abstract : A microwave plasma reactor for diamond growth that allows for highly controllable process conditions is presented. The position of the diamond substrate within the reactor can be accurately controlled. Thus, equilibration of plasma conditions can be carried out after changes in process parameters. With this approach, sharp layer transitions among doped, undoped, and isotopically controlled diamond films can be obtained. In addition to the sample transfer, the growth temperature is maintained through a substrate heater, and a clean reactor environment is realized by a load‐lock sample exchange system. The plasma conditions are constantly monitored by optical emission spectroscopy. Using this system, the growth of nanoscopic sandwich structures is demonstrated with controlled isotopic ratios down to ≈10 nm thickness and N(V) layers below 50 nm are obtained on (001)‐oriented diamond. Growth rates and doping efficiencies depending on the used methane concentration are presented. Characterization with continuous‐wave optically detected magnetic resonance yields an average contrast of 4.1% per nitrogen vacancy (NV) orientation in layers with a thickness below 100 nm. Depending on the used methane concentration, surface morphology and NV doping homogeneity are influenced as observed by photoluminescence and atomic force microscopy measurements. Abstract : A chemical vapor deposition reactor with sample transfer is presented. A lift enables an abrupt removal of the sample from plasma, interrupting the growth process. Growth resumption can then be performed by subsequent reintroduction of the sample at changed plasma compositions. This allows for sharp doping and isotope gradients in grown diamond thin films as required by diamond quantum technologies.